Social accountability challenges and recommendations by community service rehabilitation therapists - Ntandoyenkosi L. Msomi; Andrew J. Ross (South African Family Practice)
Background: Social accountability entails providing equitable and accessible services that are tailor-made for the community’s healthcare needs and enable rehabilitation therapists to improve the efficiency and efficacy of healthcare delivery and their response. Enabling them to provide optimal care during their community service year requires understanding the gaps in their knowledge, experience and the support they provide to the communities they service.